Inattentive Voters and Welfare-State Persistence - Christian Bredemeier (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Welfare-state measures often tend to persist even when they seem to have become suboptimal due to changes in the economic environment. This paper proposes an information-based explanation for the persistence of the welfare state. I present a structural model where rationally inattentive voters decide upon implementations and removals of social insurance. In this model, welfare-state persistence arises from disincentive effects of social insurance on attentiveness. The welfare state crowds out private financial precautions and with it agents' attentiveness to changes in economic fundamentals. When welfare-state arrangements are pronounced, agents realize changes in economic fundamentals later and reforms have considerable delays. – – Wohlfahrtsstaatliche Maßnahmen bleiben häufig bestehen, auch wenn sie aufgrund von Veränderungen der ökonomischen Umwelt suboptimal erscheinen. Dieser Aufsatz bietet eine informationsbasierte Erklärung für die Persistenz des Wohlfahrtsstaats an. Ich präsentiere ein strukturelles Modell, in dem rational unaufmerksame Wähler über Einführung oder Abschaffung einer Sozialversicherung entscheiden. In diesem Modell entsteht eine Persistenz des Wohlfahrtsstaats durch die Anreizeffekte der Sozialversicherung auf die Aufmerksamkeit. Der Wohlfahrtsstaat verdrängt private Vorsorge und mit ihr die Aufmerksamkeit der Agenten mit Blick auf Veränderungen der ökonomischen Umwelt. Wenn wohlfahrtsstaatliche Maßnahmen ausgeprägt sind, bemerken die Agenten Veränderungen der ökonomischen Umwelt später und Reformen haben daher ausgeprägte Verzögerungen.
Keywords: D72; H55; D83; 330; welfare state; voting; imperfect information